CHARACTERIZATION OF JAVANESE HATE SPEECH WITH LEGAL IMPACT: A FORENSIC LINGUISTIC STUD - Trismanto, tris - (Universitas 17 Agustus 1945 Semarang, 2024)
This study aims to identify and analyze the characteristics of hate speech in Javanese speech using a forensic linguistic approach. The research method is descriptive qualitative with 4 case data of alleged Javanese hate speech. Based on the analysis of the structure, meaning, and context of language use, it is found that there is a use of words with negative and insulting meanings. These utterances not only serve as a communication tool but also as a means to attack and defame someone, which can have a detrimental impact socially and reputationally. The results of this study are expected to provide a deeper understanding of the dynamics of hate speech in Javanese and its contribution to discriminatory treatment and social injustice in society. Keywords: Forensic linguistics, Hate Speech, Javanese Language